2017
DOI: 10.1242/jcs.202168
|View full text |Cite
|
Sign up to set email alerts
|

A rim-and-spoke hypothesis to explain the biomechanical roles for cytoplasmic intermediate filament networks

Abstract: Textbook images of keratin intermediate filament (IF) networks in epithelial cells and the functional compromization of the epidermis by keratin mutations promulgate a mechanical role for this important cytoskeletal component. In stratified epithelia, keratin filaments form prominent radial spokes that are focused onto cell-cell contact sites, i.e. the desmosomes. In this Hypothesis, we draw attention to a subset of keratin filaments that are apposed to the plasma membrane. They form a rim of filaments interco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
65
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 50 publications
(69 citation statements)
references
References 127 publications
4
65
0
Order By: Relevance
“…We propose that intermediate filaments provide the MC mechanical strength to support the plasma membrane to withstand the pressure from the forming vitelline membrane around over longer time period. This is in agreement with the structural role of intermediate filaments in providing mechanical strength, including plasma membrane support to cells (reviewed in Loschke et al, 2015;Quinlan et al, 2017). In addition, we observe enrichment in acetylated tubulin in the MC cytoplasmic process that pushes on the oolemma (Fig.…”
Section: What Are the Events Downstream Of Taz Driving Differentiatiosupporting
confidence: 91%
“…We propose that intermediate filaments provide the MC mechanical strength to support the plasma membrane to withstand the pressure from the forming vitelline membrane around over longer time period. This is in agreement with the structural role of intermediate filaments in providing mechanical strength, including plasma membrane support to cells (reviewed in Loschke et al, 2015;Quinlan et al, 2017). In addition, we observe enrichment in acetylated tubulin in the MC cytoplasmic process that pushes on the oolemma (Fig.…”
Section: What Are the Events Downstream Of Taz Driving Differentiatiosupporting
confidence: 91%
“…Taken together, these results indicate that desmin has no influence on the mechanical properties of the cell cortex. This was expected, as the cortex structure is mainly composed of actin and actin binding proteins, and desmin is excluded from it (see Figure ), although in some cell types a subplasmalemmal IF network has been identified [Quinlan et al., ]. However, when myoblasts overexpress functional or mutated desmin that is polymerised into networks, we show an increase in global and local stiffness as measured with the SCR and the MT.…”
Section: Resultssupporting
confidence: 70%
“…In cells, interactions between intermediate filaments are mediated by a variety of accessory proteins that crosslink the filaments to each other, 76 to actin and microtubules, 13 and to cell-matrix and cell-cell adhesions. 66 Rheological studies on reconstituted networks of intermediate filaments have furthermore shown that they are inherently associative due to ionic interactions, 63 particularly between their highly charged carboxy-terminal tail domains which act as crosslinkers. 52 As a result of this crosslinking, intermediate filament networks exhibit nonlinear stress stiffening over several decades of applied stress.…”
Section: Introductionmentioning
confidence: 99%